The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11042-019-08473-5
|View full text |Cite
|
Sign up to set email alerts
|

QoE of cross-modally mapped Mulsemedia: an assessment using eye gaze and heart rate

Abstract: A great deal of research effort has been put in exploring crossmodal correspondences in the field of cognitive science which refer to the systematic associations frequently made between different sensory modalities (e.g. high pitch is matched with angular shapes). However, the possibilities cross-modality opens in the digital world have been relatively unexplored. Therefore, we consider that studying the plasticity and the effects of crossmodal correspondences in a mulsemedia setup can bring novel insights abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
0
3
0
2
Order By: Relevance
“…Furthermore, they did find significant associations between their shapes and odors (lemon and vanilla) and an emotional dimension (arousal). Mesfin et al [48] investigated the use of crossmodally congruent olfactory stimuli in multisensory multimedia. Their results revealed that crossmodally matched media enhances the quality of experience compared to a video only condition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they did find significant associations between their shapes and odors (lemon and vanilla) and an emotional dimension (arousal). Mesfin et al [48] investigated the use of crossmodally congruent olfactory stimuli in multisensory multimedia. Their results revealed that crossmodally matched media enhances the quality of experience compared to a video only condition.…”
Section: Discussionmentioning
confidence: 99%
“…Another future direction that could be addressed in the context of authoring tools is that of crossmodal correspondences [61], which may affect our perceptual experiences. This concept refers to a compatibility effect between attributes or dimensions of a stimulus in different sensory modalities.…”
Section: Future Directionsmentioning
confidence: 99%
“…A correlation was found between these objective metrics with the arousal and subjective ratings of QoE [ 32 ]. Eye gaze data and heart rate have been analyzed for evaluating the enjoyment and perception of viewers while experiencing mulsemedia content [ 33 , 34 ]. Cross-modal correspondences were also identified when mapped with multi-sensory effects.…”
Section: Introductionmentioning
confidence: 99%